Is water fluoridation correlated with hypothyroidism? - Jarosz, Piotr Michał; Gołacki, Jakub; Matuszek, Małgorzata (Journal of Education, Health and Sport, 2022)
Introduction: Hypothyroidism is a global health problem. Primary thyroid hormone deficiency may be caused by a wide spectrum of health problems, e.g. chronic autoimmune thyroiditis, postpartum thyroiditis, iodine deficiency, thyroid or parathyroid surgery and drugs. In recent years, scientific studies have also been published indicating a correlation between excessive intake of fluoride and hypothyroidism. Fluoride is added to the water sources of many countries. Objective: The purpose of the study was to review and compare currently available data on PubMed about fluoride-induced hypothyroidism. A brief description of the state of knowledge: Evidence based knowledge suggests that there is a potential relationship between water fluoridation and endocrine system disorders, especially hypothyroidism. Current studies indicate that TSH hormone levels get elevated with increased fluoride intake. The reason is supposed to be that fluorine is more electronegative than iodine and therefore easily displaces iodine from the body, thus affecting thyroid function. Conclusions: Current studies do not clearly show a simple correlation between excessive fluoridation of drinking water and the occurrence of hypothyroidism. However, inconclusive scientific evidence and the prevalence of hypothyroidism in the population indicate the need for further research in this area.